Dual at its best deal - Fatina, Bakar; Yanti Salina, Saari (Pusat Bahasa Moden dan Sains Kemanusiaan, 2010)
4 May 2010. CMLHS nailed dual best achievements at the administrative level as well in teaching and learning arena during UMP 2010 Cendekia Bitara Ceremony which was held at Bukit Gambang Resort City. The centre was honoured with double recognitions from two of the categories contested namely the Quality Award and the Excellent Lecturer Award (for Social Sciences Category).